STAD Type Cooperative Learning Style to Improve Students' Mathematical Abilities - Rizqa Noviana Putri; Airlangga Kaivalya (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
The application of the STAD type cooperative learning method (Student Teams-Achievement Divisions) is a relevant strategy in efforts to improve students' mathematical abilities. In this research, we examine the effectiveness of using the STAD type cooperative learning style in improving students' mathematical abilities. This approach involves dividing students into small teams to encourage collaboration, joint problem solving, and knowledge exchange. We evaluated the impact of implementing this learning model on students' mathematical abilities and gained insight into effective learning strategies in the context of improving mathematics achievement.